Faculty Support as Part of Faculty Strategy on the Academic Motivation of the Working Students - Horia Mihai Raboca; Florin Cărbunărean (MDPI AG, 2024)
Working students are an important and diverse category within today's higher education institutions. Part of the strategies necessary for the academic motivation of working students and implicitly the increase of their performance concerns a series of strategies that involve individual, institutional and structural factors. This study investigates the relationship between working students perceptions of faculty support and their overall level of academic motivation (intrinsic motivation, extrinsic motivation or amotivation) grounded in self-determination theory. The findings indicated that there is a significant positive correlation between faculty support and the overall level of students' academic motivation. At the same time, the results show that both psychological and functional support, as indicators of faculty support, have strong relationships with different types of academic motivation. In this sense, our results indicate that faculty support for working students has a strong positive relationship with students' intrinsic academic motivation and respectively a weaker relationship with academic amotivation. These results show that any policy or strategy adopted by faculty decision-makers to help working students improve their academic motivation (performance) must include the provision of support on different dimensions (social, psychological and functional).